2007
DOI: 10.1124/dmd.106.013342
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Solute Carrier mRNA Expression Along the Human Intestinal Tract

Abstract: ABSTRACT:Intestinal absorption of drugs, nutrients, and other compounds is mediated by uptake transporters expressed at the apical enterocyte membrane. These compounds are returned to the intestinal lumen or released into portal circulation by intestinal efflux transporters expressed at apical or basolateral membranes, respectively. One important transporter superfamily, multiple members of which are intestinally expressed, are the solute carriers (SLCs). SLC expression levels may determine the pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
166
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(178 citation statements)
references
References 21 publications
11
166
0
1
Order By: Relevance
“…[19] However, several other reports indicate that OATP1A2 is not expressed at mRNA levels in the intestine. [12,14,35] Instead the interaction with grapefruit juice for fexofenadine could have been due to an interaction with OATP2B1. Failure of initially identifying fexofenadine (and possibly other substances) as a substrate for OATP2B1 may be explained by the pH-dependence of this transporter.…”
Section: Mrp6mentioning
confidence: 99%
See 3 more Smart Citations
“…[19] However, several other reports indicate that OATP1A2 is not expressed at mRNA levels in the intestine. [12,14,35] Instead the interaction with grapefruit juice for fexofenadine could have been due to an interaction with OATP2B1. Failure of initially identifying fexofenadine (and possibly other substances) as a substrate for OATP2B1 may be explained by the pH-dependence of this transporter.…”
Section: Mrp6mentioning
confidence: 99%
“…The intestinal expression of the absorptive transporter OATP1A2 is less evident. Two scientific papers have suggested that OATP1A2 is expressed at mRNA levels in the small intestine, and this transporter has also been [12,13] Jejunum > colon [14] Ileum [15] Ileum > duodenum [13] BCRP ABCG2 Ex Ileum > duodenum, colon [16] Duodenum > ileum > colon [17] Jejunum > colon [14,18] Duodenum [19] Jejunum [20] Small intestine [21] Duodenum = ileum = colon [22] Small intestine and colon [23] MCT1 SLC16A1 Ab Colon > duodenum > ileum [16] Colon > duodenum [24] Colon > jejunum [18] Colon > ileum [25] Jejunum = colon [15] Small intestine [21,26] Colon > ileum > jejunum [24] Colon [25] MCT3 SLC16A8 N.R. N.R.…”
Section: Intestinal Transporters For Organic Anions and Their Substramentioning
confidence: 99%
See 2 more Smart Citations
“…Carnitine/organic cation transporter OCTN1/SLC22A4, classified as a xenobiotic transporter, is ubiquitously expressed in the body, and transports various therapeutic agents including organic cations and zwitterions (Tamai et al, 1997;Meier et al, 2007;Taubert et al, 2009). However, OCTN1 has mainly been characterized in vitro, and little is known about its function in vivo.…”
Section: Introductionmentioning
confidence: 99%